Quality of measuring devices enclosed with paediatric oral liquid dosage forms of medicines registered in Sri Lanka - Abarna, N.; Sathiadas, M.G.; Sri Ranganathan, S. (PLOS, 2023)
Oral liquid dosage forms remain popular in several middle income countries. The accuracy of liquid dosage form dosing depends on the accuracy and availability of measuring devices. Lack of quality oral liquid measuring devices will lead to medication errors. Hence there is an urgent need to describe the quality of manufacturer supplied measuring devices enclosed with paediatric oral liquid dosage forms currently registered in Sri Lanka.